2020
DOI: 10.1111/mmi.14640
|View full text |Cite
|
Sign up to set email alerts
|

Alanine metabolism in Bacillus subtilis

Abstract: Bacterial cell growth requires the coordinated synthesis of all the metabolites necessary for the enlargement of the cell. One essential component of the bacterial cell wall that is unique to bacteria is D-alanine. This amino acid isomer is universally used by bacteria in the synthesis of the peptidoglycan (PG) where it acts as a substrate for penicillin binding protein-mediated crosslinking of the glycan strands (Hernandez & Cava, 2016;Lam et al., 2009). Also, in Grampositive bacteria, D-alanine is used to mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…We observed that D-met, and D-trp, have a significant effect on triggering the disassembly of the biofilms at concentrations of ≥5 mM, similar to that observed for S. aureus and P. aeruginosa [43]. It is important to note that the inhibitory effect on the growth of C. jejuni by DAs, except D-met, could be reversed by D-ala, similar to that observed for B. subtilis, M. tuberculosis and Escherichia coli [38,39,44,45].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We observed that D-met, and D-trp, have a significant effect on triggering the disassembly of the biofilms at concentrations of ≥5 mM, similar to that observed for S. aureus and P. aeruginosa [43]. It is important to note that the inhibitory effect on the growth of C. jejuni by DAs, except D-met, could be reversed by D-ala, similar to that observed for B. subtilis, M. tuberculosis and Escherichia coli [38,39,44,45].…”
Section: Discussionsupporting
confidence: 74%
“…To explore that possibility, we interrogated the effect of DAs and LAs on the expression level of two genes in C. jejuni; alanine racemase (alr) (Cj0905c), and D-Ala-D-Ala ligase (ddlA) (Cj0798c) [48,49]. Both genes are encoding enzymes involved in an important step in D-Ala metabolism [44,50], which is essential for the synthesis of PG of the bacterial cell wall [45,51,52]. Two main reactions are involved in this process, first the conversion of L-Ala to D-Ala by alanine racemase (alr), and the formation of D-alanyl-D-alanine dipeptide (D-Ala-D-Ala) from D-ala by D-alanine-D-alanine ligase (ddl) [53].…”
Section: Discussionmentioning
confidence: 99%
“…The most downregulated gene under both conditions coded for the alanine dehydrogenase (E2E30_RS03695; EC 1.4.1.1). In bacteria, this enzyme is crucial for the utilization of l- alanine as an energy source and is also involved in the transcriptional regulation of alanine metabolism ( 50 ). A complete list of up- and downregulated genes can be found in Table S5 .…”
Section: Resultsmentioning
confidence: 99%
“…The latest updates reflect intensive research to identify novel transporters in B. subtilis . These include transporters for bicarbonate (NdhF-YbcC) ( 20 , 21 ) and several amino acids, including alanine (AlaP), glutamate and serine (both AimA), and the toxic analogon glyphosate (GltT) ( 22–25 ).…”
Section: New Data Integrationmentioning
confidence: 99%